A novel method for producing LI-PS products and corresponding products
A novel synthesis method for Li-P-S products like Li7P3S11 stabilizes the compound and improves lithium battery safety by forming chemically stable, high-conductivity electrolytes without high-temperature sintering, addressing the safety and stability issues of conventional lithium batteries.
Patent Information
- Application Number
- JP2022514817
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-06
- Filing Date
- 2020-09-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-09-04
AI Technical Summary
Conventional lithium batteries using liquid electrolytes pose safety risks due to flammability and can form lithium dendrites, leading to short circuits and accidents, while existing solid sulfide electrolytes like Li7P3S11 are chemically unstable and require high-temperature sintering processes.
A new method for synthesizing Li-P-S products, particularly Li7P3S11, involves mixing Li2S and P2S5 under an inert atmosphere, heating the mixture to form Li-P-S products, and cooling them to stabilize the compound, eliminating the need for high-temperature sintering and ensuring chemical stability.
The method produces chemically stable Li-P-S products with high Li+ conductivity, suitable for lithium batteries, enhancing safety and extending battery life by preventing lithium dendrite formation and eliminating the need for high-temperature processing.
Smart Images

Figure 0007623361000003 
Figure 0007623361000004 
Figure 0007623361000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel process for producing Li-PS products, as well as to the products obtained by said process and their use, in particular as solid electrolytes. [Background technology]
[0002] Lithium batteries are used to power portable electronic devices and electric vehicles due to their high energy and power density. Traditional lithium batteries utilize a liquid electrolyte consisting of lithium salts dissolved in an organic solvent. Organic solvents are flammable, which creates a safety issue in the aforementioned system. When lithium dendrites form and pass through the liquid electrolyte medium, they can cause short circuits and generate heat, which can lead to accidents that can cause serious injuries.
[0003] Non-flammable inorganic solid electrolytes offer a solution to safety concerns, and their mechanical stability helps inhibit the formation of lithium dendrites, preventing self-discharge and heating problems and extending battery life.
[0004] Solid sulfide electrolytes are advantageous for lithium battery applications due to their high ionic conductivity and mechanical properties. These electrolytes can be pelletized and attached to electrode materials by cold pressing, eliminating the need for high temperature assembly steps. Eliminating the high temperature sintering step removes one of the challenges to using lithium metal anodes in lithium batteries.
[0005] Therefore, new solid sulfide electrolytes are needed.
[0006] Li7P3S 11 has a very high Li+ conductivity (1.4×10 at 25°C after cold pressing) -3 Scm -1) is a Li-PS product (Y. Seino, T. Ota, K. Takada, A. Hayashi, M. Tatsumisago, A sulphide lithium super ion conductor is superior to liquid ion conductors for use in rechargeable batteries, Energy Environ. Sci.7 (2014) 627-631). However, to date, this product has been manufactured by a process that requires the use of Li2S and P2S5 as reagents, which are chemically unstable in ambient atmospheres. Summary of the Invention
[0007] The object of the present invention is in particular to 11 The present invention provides a novel solid electrolyte comprising:
[0008] Another object of the present invention is to provide a method for the preparation of Li7P3S without requiring the exclusive use of Li2S and P2S5 as reagents. 11 The present invention aims to provide a novel method for producing Li-PS products such as
[0009] Another object of the present invention is to provide a method for the production of Li7P3S without the need to work in a protective atmosphere throughout the process. 11 The present invention aims to provide a novel method for producing Li-PS products such as
[0010] Thus, the present invention provides a method for producing ... pharmaceutical composition comprising at least the following steps: (a) mixing at least Li4P2S6, Li2S, and sulfur to obtain a first mixture; (b) heating the first mixture in an inert atmosphere, under vacuum, or under flowing H2S for a time and at a temperature sufficient to produce a Li-PS product; and (c) cooling and optionally pulverizing the Li-PS product. The present invention relates to a method for manufacturing a Li-PS product, including
[0011] Such a process has the potential to produce important solid sulfide electrolytes, in particular those with extremely high Li conductivity (1.4 × 10 at 25 °C after cold pressing, as mentioned above). -3 Scm -1 ) metastable glass ceramic Li7P3S 11 This is a novel synthetic route for the synthesis of
[0012] Unlike existing reaction pathways that require the use of only Li2S and P2S5 as reagents, which are not chemically stable in ambient atmosphere, this process uses another Li-PS compound (i.e. the aforementioned Li7P3S 11 The main advantage of this particular reaction is that the traditional reagents Li2S and P2S5 need to be stored in a protective atmosphere such as Ar or N, whereas Li7P3S 11 The aim of this study is to promote the possibility of using Li4P2S6 as a storage material in a dry room prior to the synthesis of Li4P2S6.
[0013] definition Throughout this specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises, comprising, includes, including" are understood to mean the inclusion of a stated element or method step or group of elements or method steps, but not the exclusion of any other element or method step or group of elements or method steps. According to a preferred embodiment, the words "comprise" and "include" and variations thereof mean "consisting only of".
[0014] As used herein, the singular forms "a," "an," and "the" include plural embodiments unless the context clearly indicates otherwise. The term "and / or" includes the meaning of "and," "or," and also all other possible combinations of the elements associated with this term.
[0015] The term "between and" should be understood to be inclusive of the points.
[0016] Ratios, concentrations, amounts, and other numerical data may be presented in a range format in this specification. Such range formats are used merely for convenience and brevity, and should be understood to be interpreted flexibly to include not only the numerical values explicitly recited as the range endpoints, but also to include all individual numerical values or subranges contained within the range as if each numerical value and subrange were explicitly recited. For example, a temperature range of about 120°C to about 150°C should be interpreted to include not only the explicitly recited endpoints of about 120°C to about 150°C, but also the subranges such as 125°C to 145°C, 130°C to 150°C, and individual amounts within the stated range, such as subquantities, e.g., 122.2°C, 140.6°C, and 141.3°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Thus, the process of the present invention results in a Li-PS product, i.e. a product containing lithium (Li), phosphorus (P), and sulfur (S).
[0018] According to one embodiment, the Li-PS product is Li7P3S 11 , Li3PS4, Li7PS6, and / or Li 9.6 P3S 12 is selected from the group consisting of:
[0019] More preferably, the Li-PS product is Li7P3S 11 It is.
[0020] As mentioned above, step (a) of the method according to the invention consists of preparing a first mixture from Li4P2S6, Li2S and sulfur.
[0021] Such steps are carried out by implementing conventional means well known to those skilled in the art.
[0022] Preferably, step (a) consists of a chemomechanical or mechanochemical reaction.
[0023] Thereafter, according to step (b), the mixture is heated in an inert atmosphere, under vacuum or under flowing H2S, for a period of time and at a temperature sufficient to produce the Li-PS product.
[0024] As mentioned above, step (b) can be carried out in an inert atmosphere or under vacuum. Step (b) can also include an additional sulfur source when the step is carried out under flowing H2S.
[0025] Such a heating step is carried out by conventional means well known to those skilled in the art, for example using a sealed quartz tube, a batch furnace, or a rotary furnace that can be operated under a flow of argon, nitrogen, or H2S.
[0026] According to one embodiment, the temperature in step (b) is comprised between 150°C and 600°C, preferably between 180°C and 220°C.
[0027] According to one embodiment, the heating in step (b) is carried out for a time comprised between 1 h and 200 h, for example between 6 h and 200 h.
[0028] Step (c) consists of cooling the product obtained after step (b). Preferably, the product is cooled until it reaches room temperature. Such a cooling step is carried out by implementing conventional means well known to those skilled in the art, for example by lowering the furnace to room temperature at a rate of 5° C. / min.
[0029] In particular, the cooling is carried out under natural cooling for a time sufficient to obtain a cooled product having a temperature of about room temperature, which in the present invention is defined as about 25°C ± 2°C.
[0030] The method of the invention may also include an additional step of pulverization, which is carried out after the cooling step, by implementing conventional means well known to those skilled in the art, for example by grinding the sample in a mortar or by applying a low-energy deagglomeration step.
[0031] After step (c), the Li-PS is then recovered by any means known to those skilled in the art, such as, for example, by sieving the powder.
[0032] According to one embodiment, the Li4P2S6 added in step (a) is obtained from the reaction between Li2S and P2S5. Such reactions are well described in the prior art and are well known to the skilled person, for example high temperature solid state reactions as described in (Solid State Ionics, 178 (2007), pp. 837-841).
[0033] The present invention also relates to a Li-PS product obtainable by the process defined above.
[0034] As mentioned above, the Li-PS product is Li7P3S 11 , Li3PS4, Li7PS6, and / or Li 9.6 P3S 12 Thus, preferably, the present invention relates to a Li7P3S obtained by the method defined above. 11 Regarding.
[0035] By carrying out the method of the present invention, Li7P3S obtained by the method of the prior art 11 Li7P3S having a crystal structure other than that of 11 A specific product of
[0036] Therefore, the present invention provides a compound of formula Li7P3S having a crystal structure and a volume V per formula unit contained at room temperature between 407 and 412 cubic angstroms, as determined by X-ray diffraction. 11 This also applies to products of.
[0037] X-ray diffraction (XRD) measurements were performed using Bragg-Brentano geometry with Cu K-alpha radiation in, for example, a D8 Bruker diffractometer. Preferred measurement conditions were 15 seconds per 0.03 degree step.
[0038] The volume per formula unit, V, is determined using the cell parameters taken at standard atmospheric pressure (101325 Pa) of the powder sample.
[0039] The volume per formula unit, V, is the lattice volume, V', divided by the number of formula units, Z, in the cell, where Z is 2 (Solid State Ionics, 178 (2007), pp. 1163-1167).
[0040] As is well known, V' is derived from the cell (lattice) parameters (a, b, c, α, β, γ). V'=abcsqrt(1+2cosα.cosβ.cosγ-cos 2 α-cos 2 β-cos 2 γ) (a, b, and c are the edge lengths (in angstroms (Å)) and α, β, and γ are the angles between them (in degrees).)
[0041] According to one embodiment, the compound of the formula Li7P3S 11 The product may also contain an amorphous phase.
[0042] Preferably, the compound according to the invention has the formula Li7P3S 11 is a product whose lattice (cell) parameters of the crystal structure, as measured by X-ray diffraction, are as follows: - a=12.40Å(by profile fitting) - b=6.04Å (by profile fitting) - c=12.52Å (by profile fitting)
[0043] According to one embodiment, the compound of the formula Li7P3S 11is a product whose lattice (cell) parameters of the crystal structure, as measured by X-ray diffraction, are as follows: - α=103.30°(by profile fitting) - β=113.25°(by profile fitting) - γ=75.07°(by profile fitting)
[0044] The invention also relates to the use of the product defined above, alone or in combination with any crystalline or amorphous conductive Li material, as a solid electrolyte.
[0045] Preferably, the present invention relates to a compound of formula Li7P3S as defined above. 11 and in particular the product having a crystal structure and a volume V per formula unit at room temperature, as determined by X-ray diffraction, comprised between 407 and 412 cubic angstroms, is used alone as a solid electrolyte.
[0046] According to one embodiment, the product can be used in combination with any crystalline or amorphous conductive Li material, such as, for example, beta Li3PS4 or glassy Li3PS4.
[0047] The present invention also relates to a solid electrolyte comprising at least one product as defined above.
[0048] Preferably, the solid electrolyte according to the invention has the formula Li7P3S as defined above. 11 in particular those having a crystal structure and a volume V per formula unit, determined by X-ray diffraction, comprised between 407 and 412 cubic angstroms at room temperature.
[0049] The present invention relates to a battery, preferably at least a Li-PS product obtained by the method of the present invention, or a Li-PS battery having a crystal structure at room temperature comprised between 407 and 412 cubic angstroms and a volume V per formula unit as measured by X-ray diffraction. 11 It also relates to lithium batteries, including those in the products.
[0050] The battery in which the product of the present invention is used may be a lithium ion or lithium metal battery.
[0051] A battery is composed of a positive electrode and a negative electrode that contain an electroactive material capable of reversibly inserting and extracting lithium ions.
[0052] When forming a positive electrode, the active material can be selected from the group consisting of metal chalcogenide complexes represented by the general formula LiMY2 (wherein M represents at least one transition metal species such as Co, Ni, Fe, Mn, Cr, Al, and V; Y represents a chalcogen such as O or S). Among these, it is preferable to use a lithium-based complex metal oxide represented by the general formula LiMO2 (wherein M is the same as above). Preferred examples of these include LiCoO2, LiNiO2, LiNi x Co 1-x O2(0 <x<1)、Lix(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2, Li(Ni 0.6 Co 0.2 Mn 0.2 )O2, Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, and the spinel structures LiMn2O4 and LiMn 1.5 Ni 0.5 O4. These active materials can be coated with inorganic or organic coatings such as LiNbO3.
[0053] Alternatively, when further forming the positive electrode, the active material has the nominal formula AB(XO4) f E 1-fwhere A is lithium and may be partially replaced by another alkali metal accounting for less than 20% of the A metal; B is a predominant redox transition metal of oxidation level +2 selected from among Fe, Mn, Ni, or mixtures thereof, which may be partially replaced by one or more further metals of oxidation levels +1 to +5, representing less than 35% of the predominant +2 redox metal, including 0; XO4 is any oxyanion, where X is any of P, S, V, Si, Nb, Mo, or combinations thereof; E is an anion of fluoride, hydroxide, or chloride; and f is the mole fraction of the XO4 oxyanion, typically comprised between 0.75 and 1.
[0054] The active material used to form the positive electrode can also be sulfur or Li2S.
[0055] When forming a negative electrode, the active material may preferably include a carbon-based material and / or a silicon-based material and / or lithium metal.
[0056] In some embodiments, the carbon-based material can be graphite, such as natural or synthetic graphite, graphene, or carbon black.
[0057] These materials may be used alone or as a mixture of two or more of them.
[0058] The carbon-based material is preferably graphite.
[0059] The silicon-based compound may be one or more selected from the group consisting of silicon, silicon carbide, and silicon oxide.
[0060] The lithium metal can be used as lithium foil or lithium powder. [Brief description of the drawings]
[0061] [Figure 1]Comparison of the XRD patterns of the simulated pattern of Li4P2S6 [1], the synthesized Li4P2S6 (Example 1), and the ball-milled product of Reaction 1 (Example 2). [Diagram 2] 1 is a comparison of Raman spectra of synthesized Li4P2S6 (Example 1), the ball milled product of reaction 1 (Example 2), crystalline Li7P3S11 formed by annealing of Example 2 (Example 3), and crystalline Li7P3S11 synthesized from conventional reagents Li2S and P2S5. [Diagram 3] A comparison of XRD patterns of crystalline Li7P3S11 synthesized by reaction 1 (Example 3), crystalline Li7P3S11 synthesized from conventional reagents Li2S and P2S5, and a simulated pattern of Li7P3S11
[11] . [Figure 4] FIG. 1 is a comparison of the XRD patterns of crystalline Li7P3S11 synthesized by reaction 1 (Example 3) and an empty sample holder with Be. [Diagram 5] 4 shows the profile fitting results for Examples 4 and 3. The Bragg positions are shown as black vertical lines, the fits are plotted as solid black lines, and the collected data are shown as open black circles. The region marked with an asterisk in FIG. 4 was excluded from the fitting as it involves the contribution of the sample holder. [Figure 6] Deconvolution of signals from structural sites PS4 3-, P2S7 4-, and P2S6 4- in the Raman spectrum of Example 3. The relative ratios of peak areas are also shown in the upper left of the figure. [Figure 7] Deconvolution of signals from structural sites PS4 3-, P2S7 4-, and P2S6 4- in the Raman spectrum of Example 4. The relative ratios of peak areas are also shown in the upper left of the figure. [Figure 8] 1 is a comparison of ionic conductivity values versus inverse temperature (1 / T) for ball milled material of Reaction 1 (Example 2), crystalline Li7P3S11 synthesized by Reaction 1 (Example 3), and crystalline Li7P3S11 synthesized from conventional reagents Li2S and P2S5. [Figure 9] A comparison of σ×T values versus inverse temperature (1 / T) for ball milled material from reaction 1 (Example 2), crystalline Li7P3S11 synthesized by reaction 1 (Example 3), and crystalline Li7P3S11 synthesized from conventional reagents Li2S and P2S5. The linear fitting to calculate the slope of the line is also shown as a solid black line. EXAMPLES
[0062] Here, the present disclosure will be described with examples, which are intended to illustrate the operation of the present disclosure and are not intended to be understood in a restrictive manner to imply any limitations on the scope of the present disclosure. Other examples are possible that are within the scope of the present disclosure.
[0063] Example 1: Li2S and P2S5 (both from Sigma Aldrich) were used as starting materials. In an Ar-filled glove box, 1.5 g of total powder with a 2:1 molar ratio was placed in a 45 mL ZrO2 jar containing 12 ZrO2 balls (3 g / ball, 10 mm diameter). The jar was sealed with scotch and parafilm to prevent exposure to air, then removed from the glove box and placed in a Fritzch Planetary Micro Mill Pulverisette7. It was ball milled for 38 hours at a rotation speed of 510 RPM with a 15-minute break every 15 minutes of grinding to prevent excessive heating of the jar. The jar was then transferred to an Ar-filled glove box and the powder was collected. The resulting white powder was then pelletized at 530 MPa using a 6 mm diameter die. The pellets were vacuum sealed in a carbon-coated quartz tube, which was then heated to 350 °C at a heating rate of 5 °C / min and kept at the same temperature for 36 hours. After the annealing step, the tube was slowly cooled to room temperature and opened in an Ar-filled glove box.
[0064] Example 2: To balance the following reaction, 400 mg of Example 1, 46 mg of sulfur, and 22 mg of Li2S (Sigma Aldrich) were mixed in an Ar-filled glove box.
[0065] Response 1: 3Li4P2S6+3S+Li2S=2Li7P3S 11
[0066] The mixture was placed in a 45 mL ZrO2 jar containing eight ZrO2 balls (3 g / ball, 10 mm diameter). The jar was sealed with scotch and parafilm to prevent exposure to air, then removed from the glove box and placed in a Retsch PM200 planetary ball mill grinding apparatus. The ball mill was milled for 76 hours at a rotation speed of 510 RPM with a 15-minute break every 15 minutes of grinding to prevent excessive heating of the jar. The jar was then transferred to an Ar-filled glove box and the powder was collected.
[0067] Example 3: Example 2 was pelletized at 530 MPa using a 6 mm diameter die. The pellets were vacuum sealed in a carbon-coated quartz tube, which was then annealed at 200° C. for 84 hours. After the annealing step, the tube was slowly cooled to room temperature and opened in an Ar-filled glove box to retrieve the sample.
[0068] Example 4 (Comparative): Li2S and P2S5 (both from Sigma Aldrich) were used as starting materials. In an Ar-filled glove box, 1.5 g of the total powder with a molar ratio of 7:3 was placed in a 45 mL ZrO2 jar containing 12 ZrO2 balls (3 g / ball, 10 mm diameter). The jar was sealed with scotch and parafilm to prevent exposure to air, then removed from the glove box and placed in a Fritzch Planetary Micro Mill Pulverisette7. The ball mill was milled for 76 hours at a rotation speed of 510 RPM with a 15 minute break every 5 minutes of grinding to prevent excessive heating of the jar. The jar was then transferred to an Ar-filled glove box and the powder was collected. The resulting white powder was pelletized at 530 MPa using a 10 mm diameter die. The pellets were vacuum sealed in a carbon-coated quartz tube, which was then annealed at 200 °C for 168 hours. After the annealing step, the tube was slowly cooled to room temperature and opened in an Ar-filled glove box.
[0069] Characterization Tools: X-ray diffraction of the samples was collected using a Bruker D8 diffractometer with CuKα radiation at room temperature. Prior to the experiment, the samples were sealed in a sample holder with Be in an Ar-filled glove box. Diffraction was collected in the 2θ range of 10°-100° for 13 h. Lattice constants were determined by fitting the diffraction profile using Full-Prof Suite. The profile fitting procedure in Example 3 and Example 4 was restricted to a shorter 2θ range (10°-28°) to increase the accuracy of the fitting, since a large number of Bragg positions in the P-1 space group at higher angles could mislead the fitting process. Small peaks due to the sample holder with Be (see Figure 4) were removed before the fitting process to increase the accuracy of the fitting.
[0070] Raman spectra were collected using a Raman DXR microscope (Thermo Fischer Scientific) with an excitation laser beam of 532 nm wavelength and low laser power of 0.1 mW to prevent excessive heating of the sample. The fitting process was performed using Omnic Software from Thermo Fischer Scientific.
[0071] Prior to impedance spectroscopy measurements, powder samples were cold pressed in an Ar-filled glove box. Examples 2 and 3 were pressed with a 6 mm diameter die at a pressure of 530 MPa, and Example 4 was pressed with a 10 mm diameter die at a pressure of 530 MPa. The pellets were then sandwiched between pre-dried carbon paper electrodes and then loaded into an airtight sample holder. AC impedance spectra were collected using a Biologic MTZ-35 frequency response analyzer. During the measurements, the AC potential of excitation was set to 50 mV for all samples. The frequency range for the measurements of Example 2 was 0.05 Hz to 30 MHz, while the range of 1 Hz to 30 MHz was applied for the measurements of Examples 3 and 4. The spectra of each sample were recorded at stable temperature values, varying between -30°C and 50°C in 10°C increments. Ionic conductivity values were obtained by fitting the data to an equivalent circuit model using ZView software. The slope of the σT vs. 1 / T plot was used to determine the activation energy values.
[0072] Experimental Results Response 1: 3Li4P2S6+3S+Li2S=2Li7P3S 11
[0073] The Bragg peaks observed in the XRD pattern of Example 1 correlate with the simulated peak positions of crystalline Li4P2S6[1] as shown in Figure 1. The Raman spectrum of Example 1 in Figure 3 shows a peak at 383 cm -1 Only the peak centered at P2S6 4-This is due to the vibration of the PS bond of the anion. [2, 3] Therefore, the sample was considered to be phase pure and was used as a precursor for reaction 1.
[0074] Reaction 1 was carried out via a mechanochemical synthesis route, and the reaction product was named Example 2. As shown in Figure 1, the product was X-ray amorphous, indicating the successful amorphization of the reagents. It is known from the literature that when Li2S (<75 at%) and P2S5 are used as reagents for the mechanochemical synthesis of Li-PS compounds, the reaction leads to the formation of X-ray amorphous products, similar to the case of Example 2 [4-10]. To date, the Li-PS compounds (i.e. Li7P3S 11 ) has never been synthesized before using a different Li-PS compound (i.e., Li4P2S6) as a precursor [6–10].
[0075] After mechanochemical reaction, P2S7 4- Part and PS4 3- The vibration of the PS bond of the site appears in the Raman spectrum of Example 2. See Figure 2. 4- A sudden decrease in the signal intensity of the unit indicates that P2S6 4- It is speculated that some of the phosphorus ions in the site were oxidized from +4 to +5 during the mechanochemical reaction. 4- The unit reacts with phosphorus at 280-300°C to reduce it to P2S6 4- It is known that it is possible to form units from 1, 2, 3, 4, 5, 7, and it was shown for the first time in reaction 1 that the process can be reversed by mechanochemical reactions.
[0076] The XRD pattern of Example 3 shows crystalline Li7P3S as evidenced by the XRD in FIG. 11The results show a correlation with the simulated pattern of
[11] . Additional peaks with lower intensity were also observed at 17.3°, 24.5°, and 25.5°. This is due to the sample holder with Be for collecting the powder pattern. A comparison of the pattern of Example 3 with the sample holder with Be is shown in Figure 4. For comparison, the XRD pattern of Example 4, synthesized using Li2S and P2S5 as precursors, is also shown in Figure 3. Several differences between Example 3 and Example 4 were noted. Sharper peaks are present in the pattern of Example 3, indicating a higher degree of crystallinity compared to Example 4. The lattice constants of Examples 3 and 4 were obtained by profile fitting. The obtained fits and Bragg positions are shown in Figure 5. In this figure, the open circles indicate the collected data and the black lines indicate the obtained profile fits. Significant differences were observed in the profile parameters of Examples 3 and 4, as well as the references from the literature
[11] . See Table 1. The lattice constant a of the unit cell of Example 3 is significantly smaller, and the alpha and gamma angles are larger compared to Example 4 and the materials reported in the literature. The beta angle of Example 3 was observed to be larger than that of the literature examples, but relatively smaller than that of Example 4. These results support the conclusion that the crystalline Li7P3S obtained by Reaction 1 11 However, it was demonstrated that the material is structurally different from the materials synthesized starting from the conventional reagents Li2S and P2S5.
[0077] [Table 1]
[0078] The Raman spectra of Examples 3 and 4 show a peak at 421 cm -1 , 404cm -1 , and 383 cm -1 In PS4 3- , P2S7 4- , and P2S6 4-This indicates the presence of bond vibrations of the site, see Figure 2. These results correlate with those published in the literature [7, 8, 10, 12-15]. To perform a semi-quantitative comparison of the amount of site in Examples 3 and 4, the spectra were fitted to three peaks centered at the reported location of the structural site [5]. The relative ratios of the peak areas were also compared. As shown in Figures 6 and 7, Examples 3 and 4 showed dramatic differences in their local structures.
[0079] PS4 in Example 3 3- / P2S7 4- The relative ratio of P2S6 was calculated to be 0.28, whereas the ratio in Example 4 deviated significantly and was recorded as 0.55. 4- It was also observed that the relative intensity of the unit peak was 2.63% lower. These results clearly indicated that the material synthesized from the reagents Li2S and P2S5 has different structural characteristics than the material synthesized from different Li-PS compounds as in reaction 1.
[0080] The ionic conductivities of Examples 2, 3, and 4 as a function of temperature (-30°C to 20°C) are shown in Figure 8. The activation energies were calculated from a plot of σT versus 1 / T using Equation 1. A linear fit of the data to calculate the slope is also shown in Figure 9: Formula 1:
number
[0081] Example 2 has an activation energy of 0.40 eV and a reaction rate of 5×10 at 20° C. -5 Scm -1 The Li7P3S obtained by annealing in the subsequent Example 2 showed a conductivity of 1. 11 After crystallization of Example 3, 6×10 -4 S.cm -1The conductivity of the sample showed a significant increase by 100 times at 20° C. The activation energy of the conductivity also decreased to 0.37 eV, which is smaller than the activation energy (0.38 eV) of Example 4 synthesized from the precursors Li2S and P2S5. -4 Scm -1 These results also show correlation with values reported in the literature [6, 14–18].
[0082] The results obtained from various characterization tools indicate that crystalline Li7P3S was synthesized using the alternative synthetic route described in reaction 1. 11 This shows that it is possible to synthesize
[0083] The product obtained according to the present invention (Example 3) is comparable to the values reported in the literature and to the crystalline Li7P3S synthesized using Li2S and P2S5 as reagents. 11 (Example 4-comparative) showed large differences in terms of lattice constants. Furthermore, the relative ratios of structural moieties in Examples 3 and 4 were calculated to be dramatically different. Impedance spectroscopy also showed that the ionic conductivities of both Examples were very similar to the materials reported in the literature. It was also noted that this is the first time in the literature that a successful reaction from one component of the Li2S-P2S5 binary system to the other component has been reported. This discovery paves the way for finding other alternative reaction pathways between different components of the binary system.
[0084] References [1] S. Neuberger, SPCulver, H. Eckert, WG Zeier, J. Schmedt auf der Guenne, Refinement of the crystal structure of Li4P2S6 using NMR crystallography, Dalt. Trans. (2018).doi:10.1039 / C8DT02619J. [2]C.Dietrich,M.Sadowski,S.Sicolo,D.A.Weber,S.J.Sedlmaier,K.S.Weldert,S.Indris,K.Albe,J.Janek,W.G.Zeier,Local Structural Investigations,Defect Formation,and Ionic Conductivity of the Lithium Ionic Conductor Li4P2S6,Chem.Mater.28(2016)8764-8773.doi:10.1021 / acs.chemmater.6b04175. [3]M.Tachez,J.Malugani,R.Mercier,R.Guy,Ionic conductivity of and phase transition in Li thiophosphate Li3PS4,Solid State Ionics.14(1984)181-185.doi:http: / / dx.doi.org / 10.1016 / 0167-2738(84)90097-3. [4]M.Tatsumisago,S.Hama,A.Hayashi,H.Morimoto,T.Minami,New lithium ion conducting glass-ceramics prepared from mechanochemical Li2S-P2S5 glasses,Solid State Ionics.154(2002)635-640.doi:10.1016 / S0167-2738(02)00509-X. [5]C.Dietrich,D.A.Weber,S.J.Sedlmaier,S.Indris,S.P.Culver,D.Walter,J.Janek,W.G.Zeier,Lithium ion conductivity in Li 2 S-P 2 S 5 glasses-building units and local structure evolution during the crystallization of superionic conductors Li 3 PS 4 ,Li 7 P 3 S 11 and Li 4 P 2 S 7,J.Mater.Chem.A.5(2017)18111-18119.doi:10.1039 / C7TA06067J. [6]Y.Seino,T.Ota,K.Takada,A.Hayashi,M.Tatsumisago,A sulphide lithium super ion conductor is superior to liquid ion conductors for use in rechargeable batteries,Energy Environ.Sci.7(2014)627-631.doi:10.1039 / C3EE41655K. [7]Y.Seino,M.Nakagawa,M.Senga,H.Higuchi,K.Takada,T.Sasaki,Analysis of the structure and degree of crystallisation of 70Li2S-30P2S5 glass ceramic,J.Mater.Chem.A.3(2015)2756-2761.doi:10.1039 / C4TA04332D. [8]Y.Aoki,K.Ogawa,T.Nakagawa,Y.Hasegawa,Y.Sakiyama,T.Kojima,M.Tabuchi,Chemical and structural changes of 70Li2S-30P2S5 solid electrolyte duringHeat treatment,Solid State Ionics.310(2017)50-55.doi:10.1016 / j.ssi.2017.08.006. [9]K.Minami,A.Hayashi,M.Tatsumisago,Crystallization Process for Superionic Li7P3S11 Glass-Ceramic Electrolytes,J.Am.Ceram.Soc.94(2011)1779-1783.doi:10.1111 / j.1551-2916.2010.04335.x.
[10] M.R.Busche,D.A.Weber,Y.Schneider,C.Dietrich,S.Wenzel,T.Leichtweiss,D.Schroeder,W.Zhang,H.Weigand,D.Walter,S.J.Sedlmaier,D.Houtarde,L.F.Nazar,J.Janek,In Situ Monitoring of Fast Li-Ion Conductor Li7P3S11 Crystallization Inside aHot-Press Setup,Chem.Mater.28(2016)6152-6165.doi:10.1021 / acs.chemmater.6b02163.
[11] H.Yamane,M.Shibata,Y.Shimane,T.Junke,Y.Seino,S.Adams,K.Minami,A.Hayashi,M.Tatsumisago,Crystal structure of a superionic conductor,Li7P3S11,Solid State Ionics.178(2007)1163-1167.doi:10.1016 / j.ssi.2007.05.020.
[12] RCXu,XHXia,ZJYao,XLWang,CDGu,JPTu,Preparation of Li7P3S11 glass-ceramic electrolyte by dissolution-evaporation method for all-solid-state lithium ion batteries,Electrochim.Acta.219(2016)235-240.doi:10.1016 / j.electacta.2016.09.155.
[13] M.Calpa,NCRosero Navarro,A.Miura,K.Tadanaga,Preparation of sulfide solid electrolytes in the Li2S-P2S5 system by a liquid phase process,Inorg.Chem.Front.
[14] Y. Wang, D. Lu, M. Bowden, PZEl Khoury, KSHan, ZDDeng, J. Xiao, J.-G.Zhang, J.Liu, Formation mechanism of Li7P3S11 solid electrolytes through liquid phase synthesis,Chem.Mater.(2018)acs.chemmater.7b04842.doi:10.1021 / acs.chemmater.7b04842.
[15] M.Calpa,NCRosero Navarro,A.Miura,K.Tadanaga,Preparation of sulfide solid electrolytes in the Li2S-P2S5 system by a liquid phase process,Inorg.Chem.Front.(2018)501-508.doi:10.1039 / C7QI00737J.
[16] I.H.Chu,H.Nguyen,S.Hy,Y.C.Lin,Z.Wang,Z.Xu,Z.Deng,Y.S.Meng,S.P.Ong,Insights into the Performance Limits of the Li7P3S11 Superionic Conductor:A Combined First-Principles and Experimental Study,ACS Appl.Mater.Interfaces.8(2016)7843-7853.doi:10.1021 / acsami.6b00833.
[17] S.Wenzel,D.A.Weber,T.Leichtweiss,M.R.Busche,J.Sann,J.Janek,Interphase formation and degradation of charge transfer kinetics between a lithium metal anode andHighly crystalline Li7P3S11 solid electrolyte,Solid State Ionics.286(2016)24-33.doi:10.1016 / j.ssi.2015.11.034.
[18] S.Ito,M.Nakakita,Y.Aihara,T.Uehara,N.Machida,A synthesis of crystalline Li7P3S11 solid electrolyte from 1,2-dimethoxyethane solvent,J.Power Sources.271(2014)342-345.doi:10.1016 / j.jpowsour.2014.08.024.
Claims
1. At least the following steps: (a) at least Li 4 P 2 S 6 And, Li 2 mixing S and sulfur to obtain a first mixture; (b) In an inert atmosphere, under vacuum, or H 2 heating said first mixture under a flow of S for a time comprised between 1 h and 200 h and at a temperature comprised between 150° C. and 600° C. to produce a Li—P—S product; and (c) cooling and optionally pulverizing the Li-P-S product. A method for producing a Li-P-S product, comprising:
2. The Li-P-S product is: Li 7 P 3 S 11 , Li 3 P.S. 4 , Li 7 P.S. 6 and / or Li 9.6 P 3 S 12 The method of claim 1 , wherein the compound is selected from the group consisting of:
3. The method according to claim 1 or 2, wherein said temperature in step (b) is comprised between 180°C and 220°C.
4. 4. The method according to any one of claims 1 to 3, wherein said heating in step (b) is carried out for a time comprised between 6 hours and 200 hours.
5. Li 4 P 2 S 6 But Li 2 S and P 2 S 5 The method according to any one of claims 1 to 4, obtained by reaction between
6. The formula Li has a crystal structure at room temperature with cell parameters taken at standard pressure and a volume per formula unit V contained within 407-412 cubic angstroms as measured by X-ray diffraction using a Bruker D8 diffractometer with CuKα radiation. 7 P 3 S 11 products.
7. 7. Use of the product according to claim 6 as a solid electrolyte, alone or in combination with any crystalline or amorphous conductive Li material.
8. A solid electrolyte comprising at least one product according to claim 6.
9. A battery comprising at least one product according to claim 6.
Citation Information
Patent Citations
Method for manufacturing inorganic material
JP2019071210A